2021
DOI: 10.1111/myc.13385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oestrogen on vulvovaginal candidosis

Abstract: Vulvovaginal candidosis (VVC) is one of the most common infectious diseases of the female reproductive tract. Approximately 75% of women experience at least one episode of VVC during their reproductive years, 1 while 40%-50% experience it twice, and nearly 5% of adult women are affected intractably and recurrently. Eighty-five to 95% of all VVC cases are caused by the commensal yeast Candida albicans. 2 In recent years, multiple in vitro and in vivo studies have demonstrated that higher levels of oestrogen aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Estrogens have multiple physiological effects such as on metabolism, menstruation, coagulation, bone health, the cardiovascular system ( 1 ) and the vaginal microbiome ( 2 ), and are also associated with adverse effects such as increasing susceptibility to candida albicans infection ( 3 , 4 ). In addition, sex steroid hormones have important neuropsychological and behavioral effects.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens have multiple physiological effects such as on metabolism, menstruation, coagulation, bone health, the cardiovascular system ( 1 ) and the vaginal microbiome ( 2 ), and are also associated with adverse effects such as increasing susceptibility to candida albicans infection ( 3 , 4 ). In addition, sex steroid hormones have important neuropsychological and behavioral effects.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen promotes the morphological transition to a hyphal form, which may increase the virulence of the fungus via NADPH oxidoreductase- or heat shock protein-90-related pathways. Estrogen enhances fungal drug resistance by upregulating the expression of C. albicans drug resistance genes or the transcription of phosphatidylinositol transfer protein 16 [ 65 ]. Estrogen also affects the intravaginally infected female host: On the one hand, estrogen affects the vaginal epithelium by causing increased glycogen production, epithelial remodeling, and increased adhesiveness (focal adhesion kinase is involved).…”
Section: Difference Of Sex and Gender Of The Human Host In Susceptibi...mentioning
confidence: 99%
“…On the other hand, estrogen affects the transepithelial migration of neutrophils (CD44, CD47, and Cxcl1 are involved) and the ability to kill neutrophils (heparan sulfate is involved). As a result, C. albicans can survive and attach to the vaginal mucosa much more easily [ 65 , 66 ].…”
Section: Difference Of Sex and Gender Of The Human Host In Susceptibi...mentioning
confidence: 99%
“…The main predisposing factor to yeast infection is the use of antimicrobial medication that destroys beneficial Lactobacillus bacteria of normal vaginal microbiota. Other common predisposing factors are diabetes, immunosuppressive conditions, and genetic predispositions, the use of glucocorticoids, oral contraceptives, or hormone replacement therapy [ 2 4 ]. In addition, women suffer more from yeast infections during pregnancy due to high estrogen levels and elevated glycogen levels in vaginal secretions [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other common predisposing factors are diabetes, immunosuppressive conditions, and genetic predispositions, the use of glucocorticoids, oral contraceptives, or hormone replacement therapy [ 2 4 ]. In addition, women suffer more from yeast infections during pregnancy due to high estrogen levels and elevated glycogen levels in vaginal secretions [ 4 , 5 ]. Some studies have shown that vulvovaginal yeast infection may be associated with the increased risk for preterm birth, and further treatment of asymptomatic infection might reduce the risk of preterm birth [ 6 ].…”
Section: Introductionmentioning
confidence: 99%